Peptidoglycan recognition protein-SD provides versatility of receptor formation in Drosophila immunity. - Wang, L; Gilbert, R; Atilano, M; Filipe, SR; Gay, N; Ligoxygakis, P (2008)
In Drosophila, the enzymatic activity of the glucan binding protein GNBP1 is needed to present Gram-positive peptidoglycan (PG) to peptidoglycan recognition protein SA (PGRP-SA). However, an additional PGRP (PGRP-SD) has been proposed to play a partially redundant role with GNBP1 and PGRP-SA. To reconcile the genetic results with events at the molecular level, we investigated how PGRP-SD participates in the sensing of Gram-positive bacteria. PGRP-SD enhanced the binding of GNBP1 to Gram-positive PG. PGRP-SD interacted with GNBP1 and enhanced the interaction between GNBP1 and PGRP-SA. A complex containing all three proteins could be detected in native gels in the presence of PG. In solution, addition of a highly purified PG fragment induced the occurrence not only of the ternary complex but also of dimeric subcomplexes. These results indicate that the interplay between the binding affinities of different PGRPs provides sufficient flexibility for the recognition of the highly diverse Gram-positive PG.